Green growth and low carbon emission in G7 countries: How critical the network of environmental taxes, renewable energy and human capital is? - Hao, Lin-Na; Umar, Muhammad; Khan, Zeeshan; Ali, Wajid (The Science of the total environment, 2021)
This study analyses the role of green growth in promoting a sustainable environment. In literature, the empirical and theoretical examination on the role of green growth in carbon dioxide (CO2) emissions is missing, especially in combination with other factors, i.e., human capital index, environment-related taxes and development of environment-related technologies. This study investigates the role of environmentally adjusted multifactor productivity growth (i.e. green growth) on CO2 emissions for G7 countries from 1991 to 2017. The study utilizes second generation panel data method(s), i.e. Cross-Sectionally Augmented Auto-regressive Distributive lag (CS-ARDL) model. The outcomes of theoretical and empirical findings indicate that both linear and non-linear term for green growth reduces CO2 emissions. Also, environmental tax, human capital and renewable energy use are found to decrease CO2 emissions. The impact of GDP growth both in short-run and long-run is environment depletion. However, our result supports the theoretical notion that green growth sustains environment quality. We obtained consistent results from panel causality test. Our results may further strengthen the belief of policymakers in developed countries on the promotion of green growth. [Display omitted] •We analyzed the effect of green growth and environmental tax on CO2 emissions.•We applied advanced panel data techniques.•Linear and non-linear term of green growth reduce CO2 emissions.•Environmental tax, renewable energy and human capital improve the environment.